2018
DOI: 10.1111/apm.12889
|View full text |Cite
|
Sign up to set email alerts
|

Tumor microenvironmental factors have prognostic significances in advanced gastric cancer

Abstract: Ahn B, Chae Y-S, Kim CH, Lee Y, Lee JH, Kim JY. Tumor microenvironmental factors have prognostic significances in advanced gastric cancer. APMIS 2018; 126: 814-821.Tumor microenvironment is important in the progression and survival of cancer cells. We evaluated the prognostic significance of tumor stroma percentage (TSP), Klintrup-M€ akinen (KM) grade, which reflects the density of inflammatory cells of the tumor, and Glasgow microenvironment score (GMS), a combination of TSP and KM grade, in advanced gastric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 27 publications
(49 reference statements)
1
23
0
Order By: Relevance
“…29 Thus, in this study, we found that a TSP of 70% was the best cut-off value to predict the prognosis of patients with DBDC, a value which was higher than those used for colorectal and gastric cancers as reported in previous studies. 9,10 Our findings suggest that the TSP cut-off value could be optimised in relation to the primary tumour.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…29 Thus, in this study, we found that a TSP of 70% was the best cut-off value to predict the prognosis of patients with DBDC, a value which was higher than those used for colorectal and gastric cancers as reported in previous studies. 9,10 Our findings suggest that the TSP cut-off value could be optimised in relation to the primary tumour.…”
Section: Discussionmentioning
confidence: 83%
“…The TSP, KM grade and GMS are determined based on the results of histological examination and can be successfully applied to predict the prognosis of patients with hollow viscus cancers, including colorectal and gastric cancer. 9,10,17,18 According to the primary site, tumours have a unique TME. Pancreatic cancer, bile duct cancer and breast cancer are the most representative examples of tumours showing desmoplastic tumour stroma.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations